The Role of Education Expenditure on Economic Growth under Recovery Regime of World Economic Crisis - @ Rambeli, Norimah Rambeli; Hashim, Emilda; Hashim, Asmawi; Jalil, Norasibah Abdul; Leh, Fauziah Che (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to investigate the role of government education expenditure on economic growth in Malaysia. This study emphasizes on the recovery regime, which is after world economic crises in 2008 as a sample of study. The augmented non-linear Cobb Douglass model is adapted for the study to achieve its objective. Moreover, the study adopts Ordinary Least Square testing procedure in investigating the determinant’s magnitude value of each variable. The result suggests that capital, unemployment and education expenditure are crucial in explaining the dependent variable, economic growth, at 95 percent significance level. In addition, the literacy rate is important in explaining the economic growth at 90 percent significance level. The study implies that augmentation of government expenditure on education is necessary in order to reduce the unemployment rate in Malaysia during crisis scenario. Realistically, well educated, technically skilled and physically fit workers will further enhance their opportunities in the job market that would lead towards the reduction in Malaysia’s unemployment. Consequently, it is recommended that government should expand its education expenditure ratio and spend more on improving the literacy rate in Malaysia. In effect, increase investments in these two promising factors are essential in the decline of unemployment level in the country in the long run. For future study, dynamic modeling is useful to examine the short run and long run relationships among the variables.